PENGEMBANGAN APLIKASI PEMILIHAN LAGU SECARA OTOMATIS BERDASARKAN POOLING SMS REQUEST (STUDI KASUS RADIO LPLL SUARA SIDOARJO) - sigit riyadi (STMIK YADIKA BANGIL, 2019)
Radio is a technology that is used for signal transmission and modulation by electromagnetic radiation (electromagnetic waves). Originally broadcast radio signals to be transmitted over either continuous wave data through amplitude modulation (AM) or frequency modulation (FM). Shipping method is called an analog signal. Furthermore, as the development of internet technology was found, and a digital signal which then changes the way radio signal transmission.Radio programming is the process of transferring voice script, which ends into a tangible result of an idea. Production of radio broadcasts are also basically sound is a blend of image creation with a series of words - voice, music and sound effects into a unified whole that is able to generate suggestions, emotions and imagination of the listener. Along with the development of information technology, on the radio program did not escape the computerized system, both in the management track, request management and event management. Kata Kunci : Poling SMS, frequensi Modulation